PENGARUH ART THERAPY MENGGAMBAR DAN MEWARNAI TERHADAP KECEMASAN MENJELANG OSCA PADA MAHASISWA PRODI D-III KEPERAWATAN INSTITUT ILMU KESEHATAN PELAMONIA MAKASSAR - Alvira Nurdin, Nurul; Hasbullah, Hasbullah; Salaman Alhidayat, Nurun (SIBATIK JOURNAL: Jurnal Ilmiah Bidang Sosial, Ekonomi, Budaya, Teknologi, Dan Pendidikan, 2026)
Anxiety is a common psychological response among nursing students, particularly before Objective Structured Clinical Assessment (OSCA), which evaluates practical clinical competence. Excessive anxiety can impair concentration, emotional regulation, and academic performance. This study aimed to examine the effect of drawing and coloring art therapy on anxiety levels before OSCA among Diploma III Nursing students at Pelamonia Institute of Health Sciences Makassar. This research employed a quantitative approach with a pre-experimental one group pretest posttest design. The population consisted of all Diploma III Nursing students of the 2024 cohort, with a sample of 30 respondents selected through purposive sampling. Anxiety levels were measured using the Hamilton Anxiety Rating Scale. Data were analyzed using univariate analysis and Paired Sample t-Test after normality testing. The results showed a significant decrease in mean anxiety scores after the intervention across three consecutive days, with statistically significant differences between pretest and posttest measurements (p < 0.05). Drawing and coloring activities provided relaxation effects and facilitated emotional expression, contributing to reduced anxiety levels. In conclusion, drawing and coloring art therapy is an effective non-pharmacological intervention to reduce pre-OSCA anxiety among nursing students and can be integrated into academic preparation programs to support students’ mental health and clinical readiness.